2019
DOI: 10.3389/fpsyg.2019.01607
|View full text |Cite
|
Sign up to set email alerts
|

Association Between White Matter Microstructure and Verbal Fluency in Patients With Multiple Sclerosis

Abstract: Verbal fluency refers to the ability to generate words quickly and efficiently according to predefined phonological or semantic criteria. Deficits in verbal fluency limit patients’ ability to communicate effectively and to function well in social setups. Multiple sclerosis (MS) patients suffer from various cognitive impairments, and some of them experience language deficits as well. The goal of this study is to examine the contribution of the dorsal and ventral language pathways to verbal fluency in MS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 109 publications
(145 reference statements)
6
46
0
Order By: Relevance
“…The Shapiro-Wilk test confirmed that the remaining scores (N=44 for each task) were normally distributed. Consistent with previous literature (Blecher et al, 2019;Kavé, 2005;Shao et al, 2014), letter-based fluency scores were lower than category-based fluency scores, and the two tasks were correlated (r = 0.53, p < 0.05, after controlling the FDR across all behavioral measures at q< 0.05; See Figure 1). Letter-based fluency was also strongly correlated with pattern-based fluency (r = 0.6, p < 0.05).…”
Section: Verbal Fluency Scoressupporting
confidence: 90%
See 4 more Smart Citations
“…The Shapiro-Wilk test confirmed that the remaining scores (N=44 for each task) were normally distributed. Consistent with previous literature (Blecher et al, 2019;Kavé, 2005;Shao et al, 2014), letter-based fluency scores were lower than category-based fluency scores, and the two tasks were correlated (r = 0.53, p < 0.05, after controlling the FDR across all behavioral measures at q< 0.05; See Figure 1). Letter-based fluency was also strongly correlated with pattern-based fluency (r = 0.6, p < 0.05).…”
Section: Verbal Fluency Scoressupporting
confidence: 90%
“…For example, category-based fluency supposedly capitalizes on the natural semantic organization of the lexicon, while letter-based fluency requires using less practiced strategies, as well as inhibiting semantically related words, making this task altogether more taxing (Basso et al, 1997). This notion is supported by consistent reports of better performance in category-based fluency compared with letterbased fluency (replicated here, and see Blecher et al, 2019;Kavé, 2005;Kavé and Knafo-Noam, 2015;Meinzer et al, 2009;Shao et al, 2014). Following the same reasoning, the morpheme-based fluency task may be even more demanding compared with the standard fluency tasks, as it requires more selective inhibition of inappropriate responses, e.g., semantic associations or inflections of previously provided words.…”
Section: Cognitive Processes Underlying the Morpheme-based Fluency Tasksupporting
confidence: 66%
See 3 more Smart Citations